2014
DOI: 10.3390/rs6075885
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration Variability and Its Association with Vegetation Dynamics in the Nile Basin, 2002–2011

Abstract: Evapotranspiration (ET) is a vital component in land-atmosphere interactions.In drylands, over 90% of annual rainfall evaporates. The Nile Basin in Africa is about 42% dryland in a region experiencing rapid population growth and development. The relationship of ET with climate, vegetation and land cover in the basin during 2002-2011 is analyzed using thermal-based Simplified Surface Energy Balance Operational (SSEBop) ET, Normalized Difference Vegetation Index (NDVI)-based MODIS Terrestrial (MOD16) ET, MODIS-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 68 publications
(98 reference statements)
3
26
1
Order By: Relevance
“…This has been depicted by a relatively strong correlation (r = 0.81) between the SSEBop ET and NDVI across several land-cover classes in the Mara Basin. The good correlations obtained in this study are stronger than the correlations reported for similar land covers in Alemu et al [10] in the Nile Basin, using a similar SSEBop algorithm.…”
Section: Seasonality Of Etcontrasting
confidence: 52%
See 2 more Smart Citations
“…This has been depicted by a relatively strong correlation (r = 0.81) between the SSEBop ET and NDVI across several land-cover classes in the Mara Basin. The good correlations obtained in this study are stronger than the correlations reported for similar land covers in Alemu et al [10] in the Nile Basin, using a similar SSEBop algorithm.…”
Section: Seasonality Of Etcontrasting
confidence: 52%
“…Their comparisons with observed ET from flux towers showed a better performance of MOD16 for cropland and woody savanna cover than SSEBop, while both models underestimate ET as compared to the observations. Alemu et al [10] also compared ET for the Nile Basin using MOD16-NB and the U.S. Geological Survey (USGS) SSEBop product for Africa and marked similar observations. On the other hand, our results show that SSEBop ET is higher than the MOD16-NB for wetland and flood plain areas and for forest covers.…”
Section: Validationmentioning
confidence: 64%
See 1 more Smart Citation
“…Potential evapotranspiration (PET) and evapotranspiration (ET) were used to represent the water-energy dynamics of land, considering their vital roles in global climate dynamics and terrestrial ecosystem productivity dynamics [12,[14][15][16]. PET and ET represent good predictors of species richness patterns [9] but are not consistent.…”
Section: Water-energy Dynamics and Remote Sensing Datasetsmentioning
confidence: 99%
“…and focused on relative spatial patterns rather than on absolute ET values, the uncertainties of the MODIS ET were considered minimal. In addition, systematic errors of remote sensing data have little impact on long-term anomalies [5].…”
Section: General Approachmentioning
confidence: 99%